THE NECESSITY AND STRUCTURAL COMPOSITION OF THE MUKHTASAR AL-WIQAYA (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article is dedicated to analyzing the necessity and structural composition of the Mukhtasar al-Wiqaya, authored by Ubaydullah ibn Mas‘ud Sadrush-Sharia Bukhari (d. 747/1346). As a condensed version of the Wiqaayat ar-Riwaya fi Masa’il al-Hidaya, the work has played a significant role in the Hanafi legal tradition, serving as a key educational tool by presenting worship and socio-legal issues in a clear and concise manner. The article examines the purpose of the work, the classification of legal terminology, its structural framework, and its significance in education, drawing on studies by scholars from the East, Turkey, the West, and Uzbekistan. The manuscript and printed versions, commentaries, and glosses of the work, as well as its influence in Central Asia and other Islamic countries, are analyzed. The study relies on the works of scholars such as Haji Khalifa, Umar Riza Qahhala, Fuad Sezgin, V.V. Bartold, and Muhammad Sadiq Muhammad Yusuf.